Financial Intermediaries and Monetary Controls - Smith, Warren L. (Quarterly Journal of Economics, 1959)
I. Introduction, 533. — II. Financial intermediaries and commercial banks, 533. — III. Possible destabilizing effects of intermediaries, 538; substitutions between money and intermediary claims, 540; portfolio shifts by intermediaries, 546. — IV. Concluding comments, 551.